2014
DOI: 10.1080/08946566.2014.881270
|View full text |Cite|
|
Sign up to set email alerts
|

Neuropsychological Profiles of Victims of Financial Elder Exploitation at the Los Angeles County Elder Abuse Forensic Center

Abstract: The current article examines neuropsychological correlates of financial elder exploitation in a sample of older adults who have been documented victims of financial elder exploitation. The purpose of this exploratory study was twofold. First, a subsample of the referrals at the Los Angeles County Elder Abuse Forensic Center (LACEAFC) was compared to community dwelling adults in terms of the specific cognitive domains linked to financial capacity including memory, calculation, and executive functioning. Next, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 6 publications
1
26
0
1
Order By: Relevance
“…Most of the people in the study reported being first victimized either in their teenage years or in their early 20's. This is in accordance with the literature in regard to younger people being more prone to being victimized in certain kinds of ways (e.g., violent crimes, drug-related crimes) than older people (Hawke et al, 2003;Wood et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Most of the people in the study reported being first victimized either in their teenage years or in their early 20's. This is in accordance with the literature in regard to younger people being more prone to being victimized in certain kinds of ways (e.g., violent crimes, drug-related crimes) than older people (Hawke et al, 2003;Wood et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…According to Kelly, Merrill, Shumway, Alvidrez, and Boccellari (2010) the major risk factors that are correlated to being victimized include being poor, living in the inner-city, living in urban public housing, being exposed to ongoing community violence, and being (Kelly et al, 2010). Additional risk factors include higher numbers of marijuana dispensaries, which has been associated with predatory crime and increased opportunities for crime (Contreras, 2017), drug use and being violently victimized (Hawke, Jainchill, & DeLeon, 2003), and being a community-dwelling elderly individual in Los Angeles and being financially abused (Wood et al, 2014). Research has also found that Black elderly men and women living in poor urban neighborhoods are especially at risk for being victimized and live in higher than average levels of fear (Bazarghan, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study of substantiated fraud victims, Wood and colleagues found that the victim sample was more likely to have a diagnosis of dementia and evidenced poorer memory, calculation abilities, and executive functioning (Wood et al, 2014). These findings are consistent with a recent report examining undue influence cases in California (Quinn, Goldman, Nerenberg, & Piazza, 2010).…”
Section: Framework and Description Of Relevant Theory And Researmentioning
confidence: 99%
“…While it is useful to know that overall cognitive ability predicts financial literacy (Earl, Gerrans, Asher, & Woodside, 2013) and that cognitive decline increases the likelihood of financial exploitation—and even the decision by prosecutors to prosecute the perpetrators (Wood et al, 2014)—general cognition may or may not be related to a specific financial judgment. It is clear that such measures are too limited to accomplish what is needed.…”
Section: Financial Decision Making In Older Adultsmentioning
confidence: 99%